PROTOTYPE LOW COST SOFTWARE DEFINED RADIO (SDR) USING RASPBERRY BOARD - Naufal Faris Saha Sika; Faridatun Nadziroh, S.ST., MT; Dr. I Gede Puja Astawa, ST., MT (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Software Defined Radio (SDR) is a radio system in which components that are typically built by Hardware (mixers, filters, modulators, demodulators, etc.) are replaced by Software. Software Defined Radio (SDR) is currently well-known among the global amateur radio community. Various Transceiver designs based on Software Defined Radio (SDR) have been widely applied, and various SDR application Software has been developed. However, the use of Software Defined Radio (SDR) requires access to the Radio Frequency Spectrum, which is one of the most expensive and scarce resources. Therefore, in this final project, the use of Raspberry Pi as a signal generator and RTL-SDR as a signal receiver is proposed, enabling the transmission of data through radio frequencies. The data transmitted includes audio, text, and images. The research results show that Raspberry Pi can be used as a radio wave transmitter through the GPIO pins of the Raspberry Pi. The signal is then received by RTL-SDR, and the results are displayed using third-party Software that generates output according to its classification. The maximum testing distance for this project is up to 15 meters, using additional antennas on the transmitter side